Surface modification and functionalization of ceramic composites - Jose, Rajan; Ezema, Fabian I. (Elsevier, 2023)
Surface Modification and Functionalization of Ceramic Composites is intended for both experts and beginners, allowing them to have an extended overview of recent progress in the evolution of surface modification methods and functionalization for ceramic composites. The book provides a detailed summary of the various techniques that are currently available, along with an evaluation of the costs involved. Information on the relationship between surface properties and function is also discussed. There is also an additional section on commercial and industrial applications, including biomedical, sensing and energy. The book will be a valuable reference resource for researchers and an instructive and stimulating text for postgraduate students who want to enhance their knowledge on novel materials and surface modification and functionalization of ceramic composites.
Keywords: Ceramic materials -- Surfaces.; Composite materials -- Surfaces.; Ceramics.; elektronické knihy; electronic books